Honey Extract Applied to Burns Has a Wound Healing Effect on Mid-Dermal Burns - Ika Syani Putri Lubis; Wahyu Indra Syohanda (Journal of Health, Medical, and Psychological Studies, 2026)
This empirical study investigates the therapeutic efficacy of wild uncultivated honey extract compared to commercial farmed alternatives and conventional silver sulfadiazine therapy on mid dermal burn wound management. Utilizing a randomized post test control group design, uniform thermal lesions were precisely induced on the dorsal region of male Wistar rats (Rattus norvegicus) to evaluate macroscopic planimetric progression, biochemical profiling, and histomorphometric tissue restoration over a fourteen day monitoring timeframe. The experimental data reveal that the primary group receiving wild uncultivated honey extract achieved a prominent wound area contraction of  on day 14, significantly outperforming the conventional therapy. Biochemical profiling confirmed that the wild matrix possessed superior total phenolic content and exceptional antioxidant capacity, which successfully disrupted Staphylococcus aureus proliferation at a remarkably low minimum inhibitory concentration. Microscopic evaluations validated that this phytochemically rich intervention stimulated an optimal fibroblast density of  cells per high power field and enhanced microvascular count. This integrated analysis demonstrates that wild honey extract effectively optimizes structural dermal repair mechanisms.